A novel approach for efficient co-expression of two foreign genes based on the reverse genetic system of Newcastle disease virus - Lan, Ting; Liu, Qilong; Ge, Jinying; Wang, Yong (Frontiers in Microbiology, 2024)
Newcastle disease virus (NDV) is an ideal model for exploring the mechanisms of the virus; it is also an optimal vector for developing vector vaccines and for cancer therapy. A reverse genetic system of NDV Mukteswar strain controlled by eukaryotic cellular RNA polymerase II promoter was established by reverse genetics technology. Based on the reverse genetic system, an open reading frame of the enhanced green fluorescent protein (EGFP) gene be inserted between the P and M genes of the viral genome and flanked with the gene start (GS) sequence and gene end (GE) sequence to form an independent transcription unit. The rescued virus was amplified in specific pathogen-free (SPF) chicken embryos for 10 generations, and the results showed that the recombinant virus could stably express the exogenous gene for at least 10 generations. Efficient expression of two exogenous genes synchronously is essential for the development of NDV-based multivalent vaccine candidates. Explore the possibility of simultaneous and efficient expression of two exogenous genes based on NDV vector. In the present study, a recombinant virus with co-expression of EGFP and cherry fluorescent protein (CFP) inserted between the intergenic regions of the P/M gene as two independent transcription units was successfully rescued. The results showed that the two exogenous genes could be expressed synchronously and efficiently. The results of biological analysis of the expression efficiency of exogenous genes showed that the EGFP in recombinant viruses with two exogenous genes was slightly lower than that of recombinant viruses with one exogenous gene, but the expression efficiency of CFP in recombinant viruses with two exogenous genes was higher than EGFP in both viruses. These recombinant viruses have similar growth kinetics but with a little attenuation in virulence compared with parental viruses. In conclusion, these data indicated that this study successfully established the reverse genetic system of the NDV Mukteswar strain and achieved the purpose of efficient expression of two exogenous genes synchronously in a novel approach, laying the foundation for the development of multivalent vaccines or tumor therapeutics using NDV as a vector.